Cnm‐Positive Streptococcus mutans and diffusion‐weighted imaging hyperintensities in acute intracerebral hemorrhage. (24th January 2021) - Shiga, Yuji; Aoki, Shiro; Hosomi, Naohisa; Nomura, Ryota; Nakamori, Masahiro; Nezu, Tomohisa; Tachiyama, Keisuke; Kamimura, Teppei; Kinoshita, Naoto; Shimomura, Ryo; Hayashi, Yuki; Matsushima, Hayato; et al.
Abstract: Background: Strains of Streptococcus mutans expressing the cell surface collagen‐binding protein, Cnm, encoded by cnm ( cnm ‐positive S .  mutans ), are associated with hypertensive intracerebral hemorrhage (ICH) and the occurrence of cerebral microbleeds (CMBs). Small diffusion‐weighted imaging (DWI) hyperintensities in patients with acute ICH are also associated with CMBs. However, the association between cnm ‐positive S .  mutans and DWI hyperintensities is unclear. Hence, this study aimed to investigate the association between cnm ‐positive S. mutans and DWI hyperintensities in patients with acute ICH. Methods: Patients with acute ICH were prospectively registered at three hospitals. Dental plaque specimens were collected within 4 days after admission, and cnm ‐positive S .  mutans was detected using the polymerase chain reaction. Magnetic resonance imaging at 14 ± 5 days after admission was used to evaluate DWI hyperintensities and CMBs. Results: A total of 197 patients were enrolled in this study. cnm ‐positive S .  mutans was detected in 30 patients (15.2%), and DWI hyperintensities were observed in 56 patients (28.4%). Patients with cnm ‐positive S .  mutans had a higher frequency of DWI hyperintensities (50.0% vs 24.6%; p  = 0.008) and a higher number of CMBs (5.5 vs 1.5; p  < 0.001) than those without cnm ‐positive S .  mutans . Multivariable logistic analysis revealed that the presence of cnm ‐positive S .  mutans was independently associated with DWI hyperintensities (OR 2.38; 95% CI 1.01–5.61; p  = 0.047) after adjusting for several confounding factors. Conclusion: This study found an association between the presence of cnm ‐positive S. mutans and DWI hyperintensities in patients with acute ICH. Abstract : Patients with acute intracerebral hemorrhage (ICH) were prospectively registered at three hospitals. Patients with cnm ‐positive Streptococcus mutans had a higher frequency of diffusion‐weighted imaging (DWI) hyperintensities and a higher number of cerebral microbleeds than those without cnm ‐positive S. mutans . This study found an association between the presence of cnm ‐positive S.   mutans and DWI hyperintensities in patients with acute ICH.